Effect of phytic acid–modified layered double hydroxide on flammability and mechanical properties of intumescent flame retardant polypropylene system. (27th October 2017) - Kalali, Ehsan Naderi; Montes, Anabel; Wang, Xin; Zhang, Lu; Shabestari, Marjan E.; Li, Zhi; Wang, De‐Yi
Abstract: Phytic acid–modified layered double hydroxide (Ph‐LDH) was synthesized via coprecipitation method and subsequently was used in polypropylene (PP) by combining with an ammonium polyphosphate (APP) via melt compounding method. The synergistic effect between APP and Ph‐LDH on the thermal stability, flammability, and mechanical properties of the resultant PP composites was investigated by thermogravimetric analysis, limiting oxygen index, vertical burning test (UL‐94), cone calorimeter tests, tensile test, and impact test. Morphologies of the chars obtained from the samples after the cone calorimeter tests were studied by scanning electron microscopy. The combination of APP and Ph‐LDH slightly influenced the impact and tensile properties of PP. Also, the synergistic effect between APP and Ph‐LDH occurred in the cone calorimeter test. Moreover, the combination of APP and Ph‐LDH produced better quality char that effectively suppressed the spread of the flame and volatile and finally extinguished the fire.